The interaction between energy intake, physical activity and UCP2 -866G/A gene variation on weight gain and changes in adiposity: an Indonesian Nutrigenetic Cohort (INDOGENIC). Issue 6 (28th March 2021) - Muhammad, Harry Freitag Luglio; Sulistyoningrum, Dian Caturini; Huriyati, Emy; Lee, Yi Yi; Muda, Wan Abdul Manan Wan
Abstract: The present study aimed to investigate an interaction between energy intake, physical activity and UCP2 gene variation on weight gain and adiposity changes in Indonesian adults. This is a prospective cohort study conducted in 323 healthy adults living in the city of Yogyakarta, Indonesia. Energy intake, physical activity, body weight, BMI, percentage body fat and waist:hip ratio (WHR) were measured at baseline and after 2 years while UCP2 -866G/A gene variation was determined at baseline. We reported that after 2 years subjects had a significant increment in body weight, BMI, body fat and reduction in WHR (all P < 0·05). In all subjects, total energy intake was significantly correlated with changes in body weight ( β = 0·128, P = 0·023) and body fat ( β = 0·123, P = 0·030). Among subjects with the GG genotype, changes in energy intake were positively correlated with changes in body weight ( β = 0·232, P = 0·016) and body fat ( β = 0·201, P = 0·034). These correlations were insignificant among those with AA + GA genotypes (all P > 0·05). In summary, we show that UCP2 gene variation might influence the adiposity response towards changes in energy intake. Subjects with the GG genotype of UCP2 -866G/A gene were more responsive to energy intake, thus more prone to weight gain due to overeating.